Metareasoning for Robots Adapting in Dynamic and Uncertain Environments - Herrmann, Jeffrey W.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book is a state of the art resource that robotics researchers and engineers can use to make their robots and autonomous vehicles smarter. Readers will be able to describe metareasoning, select an appropriate metareasoning approach, and synthesize metareasoning policies. Metareasoning for Robots adopts a systems engineering perspective in which metareasoning is an approach that can improve the overall robot or autonomous system, not just one component or subsystem. This book introduces key concepts, discusses design options for metareasoning approaches and policies, and presents approaches for testing and evaluation of metareasoning policies. After considering the conceptual design phase, it discusses how to implement metareasoning in the robot's software architecture and how to synthesize metareasoning policies. Every chapter has references to valuable works on robotics and metareasoning, and the book uses examples from the author's own research and from other research groups to illustrate these ideas. In addition, this book provides links to books and papers for readers who wish to investigate these topics further.
Introduction to Metareasoning -- Metareasoning Design Options -- Implementing Metareasoning -- Synthesizing Metareasoning Policies -- Testing Metareasoning Policies.
Keywords: Automation; Robotics; Artificial intelligence; Automation; Robotic Engineering; Artificial Intelligence